Recovery of PMOSFET NBTI under different conditions - 曹艳荣 杨毅 曹成 何文龙 郑雪峰 马晓华 郝跃 (Chinese physics B, 2015)
Negative bias temperature instability（NBTI） has become a serious reliability issue, and the interface traps and oxide charges play an important role in the degradation process. In this paper, we study the recovery of NBTI systemically under different conditions in the P-type metal–oxide–semiconductor field effect transistor（PMOSFET）, explain the various recovery phenomena, and find the possible processes of the recovery.